Leading from the North: Rethinking Northern Australia Development - Tom Brewer, Allan Dale, Rolf Gerritsen, Sharon Harwood, Bruce Prideaux, Linda Rosenman, Ruth Wallace (ANU Press, 2021)
Leading from the North aims to improve public dialogue around the future of Northern Australia to underpin robust and flexible planning and policy frameworks. A number of areas are addressed including social infrastructure, governance systems, economic, business and regional development, climate and its implications, the roles and trends in demography and migration in the region. This book not only speaks to the issues of development in Northern Australia but also other regional areas, and examines opportunities for growth with changing economies and technologies. The authors of this book consist of leading researchers, academics and experts from Charles Darwin University, The Australian National University, James Cook University, the Australian Institute of Marine Science and many other collaborative partners. Many of the authors have first-hand experience of living and working in Northern Australia. They understand the real issues and challenges faced by people living in Northern Australia and other similar regional areas. Backed by their expertise and experience, the authors present their discussions and findings from a local perspective.